Trait Impulsivity and Anhedonia: Two Gateways for the Development of Impulse Control Disorders in Parkinson’s Disease? - Houeto, Jean-Luc; Magnard, Robin; Dalley, Jeffrey W.; Belin, David; Carnicella, Sebastien (Frontiers in Psychiatry, 2016)
Apathy and impulsivity are two major comorbid syndromes of Parkinson’s disease (PD) that may represent two extremes of a behavioral spectrum modulated by dopamine-dependent processes. PD is characterized by a progressive loss of dopaminergic neurons in the substantia nigra pars compacta to which are attributed the cardinal motor symptoms of the disorder. Dopamine replacement therapy (DRT), used widely to treat these motor symptoms, is often associated with deficits in hedonic processing and motivation, including apathy and depression, as well as impulse control disorders (ICDs). ICDs comprise pathological gambling, hypersexuality, compulsive shopping, binge eating, compulsive overuse of dopaminergic medication, and punding. More frequently observed in males with early onset PD, ICDs are associated not only with co-morbid affective symptoms such as depression and anxiety, but also with behavioral traits such as novelty seeking and impulsivity, as well as with personal or familial history of alcohol use. This constellation of associated risk factors highlights the importance of inter-individual differences in the vulnerability to develop comorbid psychiatric disorders in PD patients. Additionally, withdrawal from DRT in patients with ICDs frequently unmasks a severe apathetic state, suggesting that apathy and ICDs may be caused by overlapping neurobiological mechanisms within the cortico-striato-thalamo-cortical networks. We suggest that altered hedonic and impulse control processes represent distinct prodromal substrates for the development of these psychiatric symptoms, the etiopathogenic mechanisms of which remain unknown. Specifically, we argue that deficits in hedonic and motivational states and impulse control are mediated by overlapping, yet dissociable, neural mechanisms that differentially interact with DRT to promote the emergence of ICDs in vulnerable individuals. We thus provide a novel heuristic framework for basic and clinical research to better define and treat comorbid ICDs in PD.